Positive vs. Negative E-WOM: Understanding the More Significant Role in Mediating E-Commerce Quality on Online Impulse Buying - Arissaputra, Rivaldi; Sultan, Mokh Adib; Hurriyati, Ratih; Gaffar, Vanessa; Asmara, Maisa Azizah; Sentika, Sarah (Universitas Brawijaya, Indonesia, 2024)
Electronic Word-of-Mouth (e-WOM) can convey product information about ratings, desires, requests and experiences. Therefore, it plays an important role in influencing purchases. This study aims to identify e-commerce quality, positive e-WOM and negative e-WOM on online impulse buying. E-commerce users sometimes act impulsively in purchasing after seeing some responses contained in e-WOM as information about the products. Positive product responses are not enough to convince e-commerce users to act impulsively, considering negative product responses is also an essential consideration for e-commerce users. This research uses a quantitative approach using a survey method of 315 respondents sampled from the population of e-commerce users in West Java, which was processed using smartPLS. This study found that e-commerce quality directly impacts online impulse buying, positive e-WOM, and negative e-WOM. Positive e-WOM does not directly impact online impulse buying, while negative e-WOM does. Another result shows that negative e-WOM successfully mediates the relationship between e-commerce quality and online impulse buying, while positive e-WOM fails to moderate the relationship between e-commerce quality and online impulse buying. This research contributes to e-commerce and consumer behaviour knowledge, serving as a reference for scholars by exploring how e-commerce quality relates to online impulse buying through positive and negative e-WOM among e-commerce users.